Cephalic tetanus studied with single fibre EMG. Issue 9 (September 1983) - Fernandez, J M; Ferrandiz, M; Larrea, L; Ramio, R; Boada, M
Abstract : In a case of cephalic tetanus with left facial spasms and trismus, the repetitive stimulation of the left facial nerve at 3, 10 and 20 Hz showed no facilitation or decrement. The amplitudes of the blink reflex were 50% lower on the affected side. The silent period of the masseter muscles was shortened. Concentric needle examination of the masseters and left facial EMG of the left frontalis muscle showed increased jitter and blocking in a significant proportion of the recorded potentials. Both jitter and blocking improved on higher innervation rates. All electrophysiological findings were normal on the second examination when the patient was asymptomatic. The single fibre EMG findings point to a presynaptic defect in the neuromuscular transmission in human tetanus.